Konstruksi Pemikiran Pendidikan Islam KH. Hasyim Asy’ari dalam Adab al-‘Alim wa al-Muta‘allim dan Pengaruhnya terhadap Etika Keilmuan Santri di Pesantren - Mudzakir, Muhammad Wafiq; Taroqqi, Muhammad Anwar; Ahmad Shoolihan Burhanuddin; Mannan Ni’mal Khasbi (DAS Institute, 2025)
This article discusses the construction of KH. Hasyim Asy’ari’s Islamic educational thought in Adab al-‘Alim wa al-Muta‘allim and its influence on the scholarly ethics of santri in pesantren. This study is based on the issue of declining attention to adab in the educational process, especially when learning is often directed mainly toward academic achievement, grades, and formal competencies. This research employs a qualitative approach using library research. The primary source of this study is Adab al-‘Alim wa al-Muta‘allim, while secondary sources include books, journal articles, and previous studies discussing KH. Hasyim Asy’ari’s thought, pesantren education, and Islamic scholarly ethics. The data were collected through documentation techniques and analyzed using content analysis and conceptual interpretation. The findings show that KH. Hasyim Asy’ari’s educational thought places adab as the main foundation in the pursuit of knowledge. Knowledge is not understood merely as information, but as a moral trust that must be preserved through sincere intention, respect for teachers, seriousness in learning, humility, and responsibility in its application. In the pesantren context, these values contribute to the formation of santri’s scholarly ethics through the teaching of classical texts, the exemplary role of kiai or ustaz, daily habituation, and a learning culture that emphasizes respect for knowledge. This article argues that Adab al-‘Alim wa al-Muta‘allim is not only relevant as a book of ethics, but also as an important foundation of Islamic educational thought for strengthening santri’s scholarly ethics amid the challenges of modern education.